Membangun Integritas dan Moralitas: Fondasi Kepemimpinan Kristen Menghadapi Era Post-Truth - Daniel Pesah Purwonugroho (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Post-truth is a phenomenon of subjective truth circulating within society at large, driven by technological advancements. Information disseminated widely in society often lacks prior validation. Truth in this post-truth era aligns with individual preferences without undergoing validation. Christian leaders bear a significant responsibility amidst the Christian community in this post-truth era. Integrity and morality are essential attributes for Christian leaders to navigate the post-truth era. The integrity and morality of Christian leaders should be founded upon the Biblical Word of God. Without integrity and morality, Christian leaders will struggle to guide the Christian community through this post-truth era. Christian leaders need to shine a light for the Christian community amidst this post-truth era. Through descriptive qualitative methodology, it can be concluded that integrity and morality form the foundation for Christian leaders to guide the Christian community through the post-truth era. Moral and integrity-driven leaders will instill similar moral values and integrity within the Christian community, enabling them to shine amidst the post-truth era.